1990
DOI: 10.2337/diab.39.6.690
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Aldose Reductase Inhibition on Development of Experimental Diabetic Neuropathy: Ultrastructural and Morphometric Studies of Sural Nerve in Streptozocin-Induced Diabetic Rats

Abstract: There is controversy over the efficacy of aldose reductase inhibitors in preventing the development of peripheral nerve lesions in experimental diabetes. This study was designed to show whether long-term (28-wk) inhibition of aldose reductase by ponalrestat influences structural changes in peripheral sensory nerve in rats with chronic streptozocin-induced diabetes. Sciatic nerve levels of sorbitol and fructose were significantly reduced but not completely normalized by ponalrestat treatment. myo-Inositol level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Metabolism of excess glucose through the polyol pathway is implicated in the pathogenesis of diabetic complications [31,32]. The findings of our study link this mechanism to acute changes in mesangial cell contractile function which may have relevance to the early glomerular hemodynamic changes observed in the STZ rat.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Metabolism of excess glucose through the polyol pathway is implicated in the pathogenesis of diabetic complications [31,32]. The findings of our study link this mechanism to acute changes in mesangial cell contractile function which may have relevance to the early glomerular hemodynamic changes observed in the STZ rat.…”
Section: Discussionmentioning
confidence: 60%
“…In high glucose, the significantly (p < 0.05) smaller cell size and no contractile responsiveness to endothelin-1 were normalized with ARI-509. Membrane-associated diacylglycerol, measured by a kinase specific 32 P-phosphorylation assay, in high glucose was unchanged after 3 h, but significantly increased (p < 0.05) after 24 h which was normalized with ARI-509. Protein kinase C activity, measured by in situ 32 P-phosphorylation of the epidermal growth factor receptor substrate was: increased by 32 % at 3 h of high glucose, unchanged by ARI-509; and decreased significantly (p < 0.05) at 24 h compared to cells in normal glucose, normalized by ARI-509.…”
Section: ó Springer-verlag 1998mentioning
confidence: 96%
See 1 more Smart Citation
“…In animal models, nerve fiber density is often used to verify nerve fiber degeneration (37,38). Small-diameter nerve fibers can be affected early in peripheral neuropathy, and terminal sensory nerve endings might have degenerated despite normal sural morphometry (39,40).…”
Section: Cyclooxygenase-2 and Diabetic Neuropathymentioning
confidence: 99%
“…In diabetic models, inhibitors of the first enzyme in the pathway, aldose reductase, prevent or correct nerve conduction velocity (NCV) and regeneration deficits [2][3][4][5][6][7][8][9][10][11][12][13]. Clinical trials of aldose reductase inhibitors (ARIs) have shown modest improvements in neurological symptoms, NCV, sensory measures, and an increase in nerve fibre regeneration [14-17] despite a less effective polyol pathway blockade than was found necessary for functional effects in animal studies [6,10,18].…”
mentioning
confidence: 99%